Development of a multiplex qPCR in real time for quantification and differential diagnosis of Salmonella Gallinarum and Salmonella Pullorum. Issue 6 (2nd November 2017) - Rubio, Marcela da Silva; Penha Filho, Rafael Antonio Casarin; Almeida, Adriana Maria de; Berchieri, Angelo
ABSTRACT: Currently there are 2659 Salmonella serovars. The host-specific biovars Salmonella Pullorum and Salmonella Gallinarum cause systemic infections in food-producing and wild birds. Fast diagnosis is crucial to control the dissemination in avian environments. The present work describes the development of a multiplex qPCR in real time using a low-cost DNA dye (SYBr Green) to identify and quantify these biovars. Primers were chosen based on genomic regions of difference (RoD) and optimized to control dimers. Primers pSGP detect both host-specific biovars but not other serovars and pSG and pSP differentiate biovars. Three amplicons showed different melting temperatures ( Tm ), allowing differentiation. The pSGP amplicon (97 bp) showed Tm of 78°C for both biovars. The pSG amplicon (273 bp) showed a Tm of 86.2°C for S . Gallinarum and pSP amplicon (260 bp) dissociated at 84.8°C for S . Pullorum identification. The multiplex qPCR in real time showed high sensitivity and was capable of quantifying 10 8 –10 1 CFU of these biovars.